KONSEP HIWALAH DALAM FIQH KLASIK DAN PENERAPANNYA DALAM SISTEM TRANSFER DIGITAL - Iqbal Maulana; Muhamad Zen (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
Hiwalah represents a humane mechanism of debt transfer rooted in Islamic principles of justice and solidarity. In classical fiqh, hiwalah refers to the transfer of a debtor’s obligation (muhil) to another party (muhal ‘alaih) who agrees to assume the debt. It is more than a simple adjustment of accounts, it embodies mutual help and economic balance within society. In modern times, the essence of hiwalah can be seen in bank transfers, remittance systems, and digital payment platforms such as mobile banking and e-wallets. This study explores how the classical concept of hiwalah can be adapted to digital transfer systems that dominate contemporary economic activities. Using a qualitative literature review of classical fiqh sources (Al-Mughni, Al-Mabsuth) and DSN-MUI Fatwa No.12/2000, this study finds that digital transfers may qualify as hiwalah when liability shifts legitimately between consenting parties. Such consent may occur orally, in writing, or through electronic agreement. However, if the transaction merely involves safekeeping of funds, it is more appropriately regarded as wadi‘ah. Thus, the application of hiwalah in digital systems reflects the flexibility of Islamic jurisprudence in harmonizing timeless principles with modern financial realities. The novelty of this study lies in its attempt to reinterpret classical hiwalah principles in the context of digital financial systems.